2021
DOI: 10.1186/s12939-021-01499-y
|View full text |Cite
|
Sign up to set email alerts
|

An intersectional analysis of the composite index of anthropometric failures in India

Abstract: Background Nutritional inequality in India has been estimated typically using stunting, wasting and underweight separately which hide the overall magnitude and severity of undernutrition. We used the Composite Index of Anthropometric Failure (CIAF) that combines all three forms of anthropometric failures to assess the severity of undernutrition and identify the most vulnerable social groups and geographical hotspots. Method CIAF was constructed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
15
1
Order By: Relevance
“…The rationale for this nding may be that educated fathers are better able to provide for the family's nutritional needs since they may be more aware of what their children need in terms of nutrition. Many studies found age of child, mother's age, unimmunized kids, high birth order, large family size, nuclear family, low SES,, early initiation of breast feeding, maternal early marriage, domestic violence and morbidities to be predictors of CIAF which have not been found in our study (10)(11)(12)(13)(16)(17)(18).…”
Section: Discussioncontrasting
confidence: 88%
“…The rationale for this nding may be that educated fathers are better able to provide for the family's nutritional needs since they may be more aware of what their children need in terms of nutrition. Many studies found age of child, mother's age, unimmunized kids, high birth order, large family size, nuclear family, low SES,, early initiation of breast feeding, maternal early marriage, domestic violence and morbidities to be predictors of CIAF which have not been found in our study (10)(11)(12)(13)(16)(17)(18).…”
Section: Discussioncontrasting
confidence: 88%
“…Poor parents often cannot afford a minimum diet and proper postnatal care for their children [ 41 ]. Other plausible explanations, such as increased clustering of urban poor in slums with limited access to public health and nutrition services and amenities, high population density, poor quality drinking water, inadequate sanitation facilities, are also blameworthy for the higher prevalence of severeundernutrition among the under-5 children of the poor households [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this section we outlined the changes in SAM prevalence in districts identified as hotspots for malnutrition based on a comprehensive analysis using the CIAF by Kochupurackal et al 10. Kochupurackal et al identified 111 districts clustered in four malnutrition hotspots in India that requires urgent policy intervention.…”
Section: Increasing Sam Trend In Some High-prevalence Districtsmentioning
confidence: 99%
“…SAM prevalence in NFHS-4 and NFHS-5 surveys was categorised as low, medium, high, very high and critical prevalence based on district-level mean prevalence and SD. Additionally, we examined the prevalence trend in SAM in the 111 undernutrition hotspot districts identified using the Composite Index of Anthropometric Failures (CIAF) based on the NFHS-4 data 10. Finally, the district level data set for SAM prevalence from NHFS-4 and NFHS-5 survey was linked with India spatial database with district boundaries in Quantum Geographic Information Systen(QGIS) open source software.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation